B253 Spinal anaesthesia in a patient with huntington's disease – a safe technique. (11th August 2022) - Maldonado, F; Sales, F; Fernandes, R
Abstract : Background and Aims: Huntington's Disease (HD) is a rare autosomal dominant neurodegenerative disease with a distinct phenotype, including chorea, dystonia and cognitive decline. 1 There are a limited number of case reports published describing the anaesthetic management of patients with HD. The majority describe general anaesthesia and show a high possibility of complications. 2 Reported experience with regional anaesthesia is sparse including only a few cases of successful spinal anaesthesia (SA). 3 Methods: We report the anaesthetic management of a 49-year-old patient with HD admitted for a left tibia fracture surgery using SA. The preoperative history and physical examination showed mild dysphagia, mild rigidity and severe choreiform movements in the extremities. After routine ASA monitoring, we sedated the patient with 2mg intravenous midazolam. Choreiform movements decreased after sedation allowing the lateral decubitus position for the technique. The dural puncture was successful on the first attempt. We used a 27-gauge Quincke needle with hyperbaric bupivacaine 0.5% and sufentanil to perform SA. Results: The lower limbs choreiform movements were completely abolished and optimal surgical conditions were provided. Mild choreiform movements in the upper limbs remained minimal throughout the 120-min duration of surgery and only an additional 2mg of midazolam was required for adequate patient sedation. The postoperative course was uneventful and the patient was discharged from the hospital on the third postoperative day. Conclusions: SA showed to be safe and effective for HD patients in appropriate surgical procedures for as long as 2h without compromising the patient's comfort, providing a rapid recovery and preventing the possible disadvantages of general anaesthesia.